Administration Effect of Lemon Aroma Therapy on Pain Reduction with Women in the 1st Active Phase - Sari, Silvie Permata; Amir, Aprima Yona; Rozyka, Fafelia; Herayono, Febby (PT. Riset Press International, 2024)
Pain during labor is a natural process caused by cervical dilatation, hypoxia of the uterine muscles during contractions, ischemia of the uterine corpus, stretching of the lower uterine segment, and compression of the cervical nerves. If labor pain occurs pathologically, it can trigger complications in pregnancy, one of which is prolonged labor. Data from the World Health Organization (WHO) in 2020 show that the maternal mortality rate is still high, with 295,000 women dying due to complications during pregnancy and childbirth. Prolonged labor is one of the fifth causes of maternal death in the world, accounting for 8.5% of cases. Pain can be relieved pharmacologically and non-pharmacologically, with one non-pharmacological method being lemon aromatherapy. This study aims to determine the effect of lemon aromatherapy on reducing pain intensity in the active phase of the first stage of labor at Painan Hospital in 2023.This research used a quasi-experimental design with a non-equivalent control group pretest-posttest. The study was conducted in July 2023, using both primary and secondary data. The sample consisted of 30 respondents selected through total sampling techniques. Data analysis was performed using Wilcoxon and Mann-Whitney non-parametric statistical analysis techniques.The results of the study showed that most participants in the intervention group experienced controlled severe pain before and after the intervention, while the control group mostly experienced moderate pain before the intervention and uncontrolled severe pain after the intervention. The Mann-Whitney test indicated a significant difference in pain intensity between the intervention and control groups, with a p-value of 0.000 < α (0.05), leading to the rejection of the null hypothesis.The researchers recommend that health services provide support to mothers experiencing pain during labor to ensure a comfortable birthing process.